Burial Customs and Society in Late Bronze and Early Iron Ages of Northwest Lithuania - Muradian, Lijana (Archaeologia Lituana, 2017)
This article investigates the burial customs of the Late Bronze and Early Iron Ages in the territory of northwest Lithuania, focusing on barrow mounds and individual grave settings and grave goods. More than a century of excavations yielded 19 burial sites, in which 182 graves are known (169 cremations and 13 inhumations). The gathered data regarding burial customs consist of grave settings, burial locations within the mounds and grave goods, and these are used to interpret some features of how the communities were socially organized. During the Late Bronze and Early Iron Ages, the dead were buried in different types of graves: barrow mounds and flat graves; individual graves had different stone arrangements in both of mentioned types. This work presents a hypothesis that different types of graves and stone arrangements associated with burials were not just a result of time-related burial customs changes, but it could be an indicator of the social identity of the deceased. It is one of the possible indicators that hierarchic societies existed during the period in question.Keywords: Late Bronze Age, Early Iron Age, barrow mounds, cremation burials, inhumation burials, society, northwest Lithuania